An overview of waste crime, its characteristics, and the vulnerability of the EU waste sector. Issue 2 (February 2014) - Baird, J; Curry, R; Cruz, P
While waste is increasingly viewed as a resource to be globally traded, increased regulatory control on waste across Europe has created the conditions where waste crime now operates alongside a legitimate waste sector. Waste crime, is an environmental crime and a form of white-collar crime, which exploits the physical characteristics of waste, the complexity of the collection and downstream infrastructure, and the market opportunities for profit. This paper highlights some of the factors which make the waste sector vulnerable to waste crime. These factors include new legislation and its weak regulatory enforcement, the economics of waste treatment, where legal and safe treatment of waste can be more expensive than illegal operations, the complexity of the waste sector and the different actors who can have some involvement, directly or indirectly, in the movement of illegal wastes, and finally that waste can be hidden or disguised and creates an opportunity for illegal businesses to operate alongside legitimate waste operators. The study also considers waste crime from the perspective of particular waste streams that are often associated with illegal shipment or through illegal treatment and disposal. For each, the nature of the crime which occurs is shown to differ, but for each, vulnerabilities to waste crime are evident. The paper also describes some approaches which can be adopted by regulators and those involved in developing new legislation for identifying where opportunities for waste crime occurs and how to prevent it.